2021
DOI: 10.1007/s13193-021-01302-y
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Early Impact of COVID-19 on Presentation and Management of Oral Cancers – an Experience from a Tertiary Care Hospital in South India

Abstract: Oral cancers are the leading cause of cancer-related death in Indian men. Currently steps to contain the transmission and treatment of COVID-19 pandemic have crippled the entire health care system. With hospitals running short of resources, the oncological practice became standstill, especially during the initial phase. This is a retrospective study among patients who presented to our tertiary care hospital in early 3 months of COVID-19 era(ECE) with respect to pre-COVID-19 era(PCE). The study includes patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(24 citation statements)
references
References 10 publications
1
21
2
Order By: Relevance
“…Similar findings were seen in patients presenting at a major cancer center in the United States; there was a statistically significant increase in tumor size and T stage seen in the early months of the pandemic (May-June 2020) compared to the same period from 2019 [12]. In addition, in a study specific to oral cancers, an analysis of patients at a tertiary care hospital in South India found a statistically significant increase in advanced T stage from April 2020 through June 2020 compared to the same period from 2019 [9]. The same was also true in a series of oral cavity cancer patients treated at Heidelberg University Hospital in Germany in 2020 when compared to patients from 2010-2019 [8].…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Similar findings were seen in patients presenting at a major cancer center in the United States; there was a statistically significant increase in tumor size and T stage seen in the early months of the pandemic (May-June 2020) compared to the same period from 2019 [12]. In addition, in a study specific to oral cancers, an analysis of patients at a tertiary care hospital in South India found a statistically significant increase in advanced T stage from April 2020 through June 2020 compared to the same period from 2019 [9]. The same was also true in a series of oral cavity cancer patients treated at Heidelberg University Hospital in Germany in 2020 when compared to patients from 2010-2019 [8].…”
Section: Discussionmentioning
confidence: 97%
“…The number of diagnostic procedures for detecting cancer and patients diagnosed with several different types of cancer, including breast, colorectal, lung, pancreatic, and gastric cancers, was lower than the numbers prior to the pandemic [11]. Specifically for head and neck cancers, two studies demonstrated a decrease in the number of patients presenting for care of head and neck cancers in the early months of the pandemic [9,12]. Our study showed similar findings; there was a decrease in the number of consults per month between January 2020 and May 2020, decreasing from 12 consults per month to 1 consult per month.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our cohort, we noticed a slight prolongation (median 15 weeks, not statistically significant) from the first symptom related to the oncologic disease till diagnosis, reflecting limitations in primary care or a change in patients’ behaviour [ 3 ]. Significant delays in cancer diagnosis have been observed in Turkey [ 18 ] and India [ 19 ], indicating compromised accessibility to health services (Table 3 ). On the other hand, in the USA [ 20 ], the median duration of the first visit remained constant at 12 weeks.…”
Section: Discussionmentioning
confidence: 99%
“…Five out of seven published studies reported more advanced T-and N-stages of HNC patients during the pandemic [18][19][20]22,24]. Despite severe pressure on health services in northern Italy during the beginning of the virus spread, D'Ascanio et al [25] did not notice any shift to more advanced cancer stages during this period.…”
Section: Article (Country)mentioning
confidence: 94%